Pengendalian Persediaan Kompresor Kaishan Kombina Metode TS dan EOQ di PT. Karya Teknik Semesta - Nia Kurniasih; Soleh Sofyan; Patria Adhistian (CV. Ulil Albab Corp, 2024)
The study entited anaysis of merchandise inventory control compressor product of Kaishan at PT. Karya Teknik Semesta in Jakarta 2023. This event will be based on research from compressor orders made with to little or too much quantity, and orders that are not properly scheduled. Which led to the company losing saes at the end of 2022, which resulted in a shortage of inventory in Januari 2023. The purpose of this research is to know how many demand for compressor products for the next period using the Time Series method, how many orders to be done each time (EOQ), the amount of safety stock (SS), and reordering point (ROP). The data obtained are then processed bt the comparing severa methods included in the Time Series method, namely; Moving Average (MA), Weight Moving Average (WMA), Exponentia Smoothing. To obtain the smalest Mean Absolute Deviation (MAD) which will be used to caculate demand forcasting for the next period. From the result of the anaysis the Time Series, EOQ, SS, and ROP, inventory costs are more efficient than the past two years (2021 and 2022).